The financial rout of Sears Canada: The tip of the financialisation iceberg - Berthelot, Sylvie; Coulmont, Michel (Management international / International Management / Gestiòn Internacional, 2022)
For a number of years, many firms’ business models have been moving toward financialisation. To the detriment of their industrial and commercial activities, companies are focusing more and more on financial transactions that maximize short-term shareholder value. Sears Canada is one example. The company that was a Canadian flagship sought protection under the Companies’ Creditors Arrangement Act in the summer 2017, to be liquidated at a later date. Our study examines the practices of shareholders and the board of directors as well as the financial arrangements that led to such a financial collapse.